SAFETY OF WOMEN ACROSS THE GLOBE: AWARENESS, SECURITY, AND SELF-DEFENCE — DEVELOPING UZBEKISTAN’S FIRST SAFETY APP - Farzona Abdumuxtorova Azizbekovna (Modern American Journals, 2025)
Issues of women’s safety remain a pressing concern across the world. Regardless of geographical, cultural, or social boundaries, women continue to experience threats ranging from street harassment to gender-based violence. These issues often extend into daily activities such as walking alone at night, commuting, or even attending public events. In Uzbekistan, as in many other contexts, conversations around women’s safety are limited, yet young women frequently report feelings of vulnerability in public spaces.